Understanding and Mapping Community Health Literacy on basic Life Support in Semi-Rural Indonesia - Rahmania Ambarika; Novian Mahayu Adiutama; Novita Ana Anggraini (Universitas STRADA Indonesia, 2026)
Background: Basic Life Support (BLS) is a fundamental life-saving skill whose effectiveness heavily relies on the ability of community members to act as first responders. Public health literacy regarding BLS serves as a critical link in the chain of survival, especially during the pre-hospital phase. Purpose: However, there is a lack of comprehensive spatial mapping of BLS literacy levels at the community level, particularly in rural areas such as Wajak Subdistrict, Malang Regency. This study aims to map the level of public health literacy concerning BLS, identify influencing factors, and provide an evidence-based foundation for preventive policymaking in primary healthcare settings. Methods: A descriptive quantitative cross-sectional study was conducted involving 400 respondents aged 17 years. Participants were selected using a cluster random sampling technique based on the smallest administrative units (neighborhoods or hamlets), ensuring geographic and demographic representation. The minimum sample size was determined using the Slovin formula with a 5% margin of error, resulting in a required minimum of 400 respondents to accurately reflect the target population distributionThe research instrument was a BLS literacy questionnaire encompassing. Data were analyzed using chi-square tests and spatially using QGIS software. Results: The majority of respondents (49.5%) demonstrated a moderate level of BLS literacy, while 34.5% showed low literacy and only 16% achieved a high level. Literacy levels were positively associated with educational attainment, prior BLS training, and age group. Spatial analysis revealed clusters of low literacy concentrated in the southern villages of the region. Conclusion: BLS literacy among the population in the Wajak area remains uneven, with vulnerable clusters requiring targeted, community-based interventions. These findings highlight the urgency of mainstreaming BLS training into public health outreach programs and integrating emergency literacy as an indicator of primary care readiness.